‘Serene Classroom’ Minimizes Noise for More Conducive Learning - Haron, Zaiton; Yahya, Khairulzan; Darus, Nadirah; Mohd Yussup, Rafidah; Awang, Abdullah Zawawi; Hussien, Norelyza; Mazlan, Ain Naadia; Zakaria, Rozana; Ismail, Mohammad; Amir Nizam, Noramera Nabila; A Kassim, Ahmad Syakir Farhan; Malek, Nur Syalyana; Rifki, Rifa Rafida; Kamaludin, Helmi; Yaakob, Syamsul Hafiz; Haron, Zaliza; Sheikh Ahmad, Sheikh Izat Azhar (ASEAN Journal of Community Engagement, 2021)
Noise pollution can be categorized as a danger in silence. In school, noise pollution inhibits the focus of learning, impairs learning and cognitive development, for example, students' skills to think and understand both oral and written comprehension may be hampered by noise. Many schools in Malaysia experience excessive noise pollution as their locations are very near busy roads. This will be one factor that hinders the implementation of the education system in producing holistic students in order to prepare for the 4IR era. Knowing the importance of this problem, a group of researchers from UTM GREENPrompt, School of Civil Engineering, Universiti Teknologi Malaysia together with industry partners have built a special class called 'Serene Classroom' through a community project to overcome this problem. A classroom on the second floor of Sekolah Kebangsaan Kampong Pasir, Johor Bahru that has traffic noise exposure from the Skudai-Johor Bahru highway was selected for this purpose. The community project is in collaboration with the Johor State Education Department, Ministry of Education Malaysia and industrial partners, such as Vibrant Echo Company, Sanjung Sempurna Sdn. Bhd. and DZAZ Collection. The implementation of the project, the lessons learned from the project and challenges for the implementation are discussed. Technically, Serene classrooms significantly reduce the level of noise pollution for more conducive learning and have received better perceptions from students and teachers. Therefore, hopefully more ‘Serene Classroom’ community projects can be implemented in schools, especially in urban areas affected by high noise levels as a way to reduce the renovation costs on schools.